Disparities in preterm birth following the July 1995 Chicago heat wave - Gordon, Milo; Casey, Joan A.; McBrien, Heather; Gemmill, Alison; Hernández, Diana; Catalano, Ralph; Chakrabarti, Suman; Bruckner, Tim (Annals of epidemiology, 2023)
To evaluate if changes in preterm birth (PTB, <37 weeks of gestation) incidence differed between non-Hispanic (NH) Black and NH white births following the July 1995 Chicago heat wave—among the most severe U.S. heat waves since 1950. We used an ecologic study design. We obtained birth data from January 1990–December 1996 from the National Vital Statistics File to calculate the mean monthly PTB incidence in Chicago’s Cook County, Illinois. Births between July 1995 and February 1996 were potentially exposed to the heat wave in utero. We generated time series models for NH Black and NH white births, which incorporated synthetic controls of Cook County based on unexposed counties. We ran a secondary analysis considering socioeconomic status (SES). From 1990–1996, the mean monthly PTB incidence among NH Black births was 18.6% compared to 7.8% among NH white births. The mean monthly PTB incidence among NH Black births from August 1995–January 1996 was 16.7% higher than expected (three additional PTBs per 100 live births per month [95% confidence interval (CI): 1, 5]). A similar increase occurred among low-SES NH Black births. No increase appeared among NH white births. Severe heat waves may increase racial disparities in PTB incidence.